Surface Passivation and Detrimental Heat-Induced Diffusion Effects in RbF-Treated Cu(In,Ga)Se2 Solar Cell Absorbers - Elizabeth, Amala; Sahoo, Sudhir K.; Phirke, Himanshu; Kodalle, Tim; Kühne, Thomas D.; Audinot, Jean-Nicolas; Wirtz, Tom; Redinger, Alex; Kaufmann, Christian A.; Mirhosseini, Hossein; Moenig, Harry (ACS Applied Materials and Interfaces, 2022)
Alkali postdeposition treatments of Cu(In,Ga)Se2 absorbers with KF, RbF, and CsF have led to remarkable efficiency improvements for chalcopyrite thin film solar cells. However, the effect of such treatments on the electronic properties and defect physics of the chalcopyrite absorber surfaces are not yet fully understood. In this work, we use scanning tunneling spectroscopy and X-ray photoelectron spectroscopy to compare the surface defect electronic properties and chemical composition of RbF-treated and nontreated absorbers. We find that the RbF treatment is effective in passivating electronic defect levels at the surface by preventing surface oxidation. Our X-ray photoelectron spectroscopy (XPS) data points to the presence of chemisorbed Rb on the surface with a bonding configuration similar to that of a RbInSe2 bulk compound. Yet, a quantitative analysis indicates Rb coverage in the submonolayer regime, which is likely causing the surface passivation. Furthermore, ab initio calculations confirm that RbF-treated surfaces are less prone to oxidation (in the form of Ga, In, and Se oxides) than bare chalcopyrite surfaces. In addition, elemental diffusion of Rb along with Na, Cu, and Ga is found to occur when the samples are annealed under ultrahigh vacuum conditions. Magnetic sector secondary ion mass spectrometry measurements indicate that there is a homogeneous spatial distribution of Rb on the surface both before and after annealing, albeit with an increased concentration at the surface after heat treatment. Depth-resolved magnetic sector secondary ion mass spectrometry measurements show that Rb diffusion within the bulk occurs predominantly along grain boundaries. Scanning tunneling and XPS measurements after subsequent annealing steps demonstrate that the Rb accumulation at the surface leads to the formation of metallic Rb phases, involving a significant increase of electronic defect levels and/or surface dipole formation. These results strongly suggest a deterioration of the absorber−window interface because of increased recombination losses after the heat-induced diffusion of Rb toward the interface.( Figure presented)
CRIS-Team Scopus Importer:2023-03-20
Keywords: chalcopyrite solar cell; RbF postdeposition treatment; scanning tunneling spectroscopy; surface passivation; X-ray photoelectron spectroscopy